2018
DOI: 10.22256/pubvet.v12n6a101.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteraciones conductuales y fisiológicas en perros detectores bajo la influencia del estrés de confinamiento

Abstract: The present article aimed to study the physiological and behavioral effects on the olfactory performance of police dogs, after everyday stress situations that occurred before to the execution of the task of detecting drugs and explosives. The effect of stress was studied from the simulation of confinement of these animals to the detection of drugs or explosives, at different transport times, using three types of confinement in transport boxes, 30 minutes (30 minutes), 3 hours and 30 minutes (03'30 ") and 5 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…A study conducted at the Central Kennel of the Federal Police of Brazil showed that the 3-hour confinement was sufficient to increase cortisol concentrations. Subsequently, cortisol concentrations decreased after the completion of the detection tasks, indicating that the longer the confinement time, the higher the cortisol concentrations and that the search and detection work probably functions as a welfare and balance promoter of the dog (MACHADO et al, 2018).…”
Section: Welfare Of Narcotics Detection Dogsmentioning
confidence: 99%
“…A study conducted at the Central Kennel of the Federal Police of Brazil showed that the 3-hour confinement was sufficient to increase cortisol concentrations. Subsequently, cortisol concentrations decreased after the completion of the detection tasks, indicating that the longer the confinement time, the higher the cortisol concentrations and that the search and detection work probably functions as a welfare and balance promoter of the dog (MACHADO et al, 2018).…”
Section: Welfare Of Narcotics Detection Dogsmentioning
confidence: 99%
“…Isso foi possível ser verificado uma vez que os níveis de cortisol tanto dosados no período de descanso quanto no período de trabalho, até o momento ainda não havia sido avaliado por outros autores. Alguns trabalhos verificaram apenas os níveis de cortisol durante o período de trabalho(BAPTISTA SOBRINHO et al, 2009;DIVERIO et al, 2016;MACHADO;MONTANHA;SILVA, 2018). Outros autores não verificaram alterações significativas no período nos quais os cães desempenhavam suas atividades policiais(HAVERBEKE et al, 2008;ARCURI, 2016).…”
unclassified